Allosteric activation of preformed EGF receptor dimers by a single ligand binding event - Purba, Endang R.; Saita, Ei-ichiro; Akhouri, Reetesh R.; Öfverstedt, Lars-Goran; Wilken, Gunnar; Skoglund, Ulf; Maruyama, Ichiro N. (Frontiers in Endocrinology, 2022)
Aberrant activation of the epidermal growth factor receptor (EGFR) by mutations has been implicated in a variety of human cancers. Elucidation of the structure of the full-length receptor is essential to understand the molecular mechanisms underlying its activation. Unlike previously anticipated, here, we report that purified full-length EGFR adopts a homodimeric form in vitro before and after ligand binding. Cryo-electron tomography analysis of the purified receptor also showed that the extracellular domains of the receptor dimer, which are conformationally flexible before activation, are stabilized by ligand binding. This conformational flexibility stabilization most likely accompanies rotation of the entire extracellular domain and the transmembrane domain, resulting in dissociation of the intracellular kinase dimer and, thus, rearranging it into an active form. Consistently, mutations of amino acid residues at the interface of the symmetric inactive kinase dimer spontaneously activate the receptor in vivo. Optical single-molecule observation also demonstrated that binding of only one ligand activates the receptor dimer on the cell surface. Based on these results, we propose an allosteric model for the activation of EGFR dimers by ligand binding. Our results demonstrate how oncogenic mutations spontaneously activate the receptor and shed light on the development of novel cancer therapies.